Investigations on some microbiological and chemical features of Kurut - Patir, B; Ates, G (Tubitak Scientific & Technological Research Council Turkey, 2002)
The microbiological and chemical qualities of kurut which is made from dried yoghurt with solar heat in some rural regions of Anatolia were studied For this aim 25 kurut samples from the Elazig area were investigated Colony forming units of mesophile aerobes coliform Staphylococcus-Micrococcus Lactobacillus Leuconostoc Pediococcus Lactococcus yeast and mould on average were 3 40x10(4)/g 2 79 x 10(2)/g 2 40 x 10(3)/g 2 23 x 10(4)/g 1 13 x 104/g and 1 12 x 10(4)/g respectively Twelve percent of samples contained Escherichia colt 1 and 16% had Staphylococcus aureus microorganisms The pH acidity (as lactic acid) moisture fat fat content of dried matter salinity salt content of dried matter and ash of the samples on average were 4 26 2 40% 10 96% 32 90% 37 14% 12 85% 14 41 % and 11 79% respectively The correlation between the general mesophile aerobe counts and dry matter were negative and strong (r = 0 84) These correlations for Lactobacillus Leuconostoc Pediococcus Lactococcus and yeast and mould microorganisms were r = 0 82 r = 0 81 and r = 0 83 respectively In addition the correlation between coliform group microorganisms and NaCl was found to be negative (r = 0 51) and Staphylococcus Micrococcus microorganisms were positive (r = 0 62) and moderate It is concluded that kurut contained considerable amounts of pathogen microorganisms such as Escherichia coli 1 and Staphylococcus aureus and was prepared and stored under unhygienic conditions Chemical analysis shows that kurut has low moisture but very high fat salt and ash contents.
Keywords: kurut; microbiological; chemical; feature